The International Financial System and Developing Country Debt Management: The Process, Problems and Prospects - Sigur, Paul (Tufts Archival Research Center, 2005)
Volume 7, Issue 1. Winter As developing countries sink further into debt and lender countries become increasingly aware of the implications of large scale defaults, the international community is devoting greater attention to the question of debt management. In this article, Paul Sigur casts the main actors involved in international lending and borrowing, discusses the mechanism for debt rescheduling and analyzes three representative case studies of debt management. Sigur argues that the international financial system, though imperfect, has successfully dealt with debt crises and will continue to do so despite occasional fears of international financial collapse. The author concludes with some suggested reforms for the debt management process and a forecast of future developments.